Development of dialectical thinking in education - Eugeny E. Krasheninnikov; Larisa F. Bayanova (Современное дошкольное образование)
Background. The article presented as a discussion brings up the variety of relevant topics on the dialectical thinking formation: “Why is the modern education not interested in developing the dialectical thinking?”; “If based on the dialectical and formal logic, will educ programs be marked with internal inconsistencies?”; “Can psychology define the operational structure of dialectical thinking as well as in the theory of formal-logical thinking?” The discussion emphasises that digitization calls for new didactic methods to build a mind able to find flexible solutions in contradictory situations.